2016
DOI: 10.3390/rs8110883
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel-2A MSI and Landsat 8 OLI Provide Data Continuity for Geological Remote Sensing

Abstract: Sentinel-2A MSI is the Landsat-like spatial resolution (10-60 m) super-spectral instrument of the European Space Agency (ESA), aimed at additional data continuity for global land surface monitoring with Landsat and Satellite Pour l'Observation de la Terre (SPOT) missions. Several simulation studies have been conducted in the last several years to show the potential of Sentinel-2A MSI (MultiSpectral Instrument). Now that real data are available, the first confirmations of this potential and comparisons with oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(86 citation statements)
references
References 41 publications
3
79
0
4
Order By: Relevance
“…As pointed out by recent works [8], although a clear similarity between the image products of Landsat and Sentinel sensors can be observed by a visual inspection, when numerical values are compared, some band combinations can show differences, which are to be evaluated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As pointed out by recent works [8], although a clear similarity between the image products of Landsat and Sentinel sensors can be observed by a visual inspection, when numerical values are compared, some band combinations can show differences, which are to be evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Clearly, the importance of these differences depends on the application and on the approach adopted to perform time series analyses or change detection. Methods based on physical quantities retrieved by remote sensing reflectance or empirical approaches based on multispectral indices are more affected by the problem [8]. Conversely, methods based on separate classification of every image are less affected, if the training is also independent [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a root mean square error (RMSE) greater than 8% in the red band was found when comparing Sentinel and Landsat simulated data, due to the discrepancies in the nominal relative spectral response functions (RSRF) [70]. Werff compared Sentinel-2A MSI and Landsat-8 OLI Data [71], finding the correlation of their TOA reflectance products is higher than their bottom-of-atmosphere reflectance products. Besides, the combined use of multi-temporal images requires an accurate geometric registration, i.e., pixel-to-pixel correspondence for terrain-corrected products.…”
Section: Cloud-free Satellite Imagery Composition At 30-m Resolutionmentioning
confidence: 99%
“…Fernandez-Manso et al (2016) and Navarro et al (2017), among others, have evaluated burn severity based on Sentinel-2 MSI data successfully. Additionally, recent studies (Shoko and Mutanga, 2017;van der Werff and van der Meer, 2016) have showed the suitability and even superiority of Sentinel-2 MSI data in natural resources applications.…”
Section: Introductionmentioning
confidence: 99%